Ca2+ sensitization and Ca2+ entry in the control of blood pressure and adrenergic vasoconstriction in conscious Wistar-Kyoto and spontaneously hypertensive rats - Behuliak, Michal; Pintérová, Mária; Bencze, Michal; Petrová, Miriam; Líšková, Silvia; Karen, Petr; Kuneš, Jaroslav; Vaněčková, Ivana; Zicha, Josef (Journal of hypertension, 2013)
BACKGROUND: Calcium entry through nifedipine-sensitive L-type voltage-dependent calcium channels (L-VDCC) is augmented in spontaneously hypertensive rats (SHR) characterized by enhanced sympathetic vasoconstriction. However, the changes of calcium sensitization mediated by RhoA/Rho kinase pathway are less understood. METHODS AND RESULTS: The participation of calcium entry and calcium sensitization in the control of blood pressure (BP) and vascular contraction was studied in SHR and normotensive Wistar-Kyoto (WKY) rats. The acute administration of fasudil (Rho kinase inhibitor) caused BP decrease which lasted longer in SHR. Fasudil also attenuated adrenergic contraction in femoral or mesenteric arteries of WKY and SHR. BP reduction elicited by fasudil in WKY was more pronounced than that induced by L-VDCC blocker nifedipine (-33±2 vs. -15±3% of baseline BP, P<0.001), whereas both inhibitors were similarly effective in SHR (-36±4 vs. -41±2%). Fasudil pretreatment also attenuated BP elevation elicited by L-VDCC agonist BAY K8644 more in WKY than in SHR (-63±4 vs. -42±5%, P<0.001), indicating reduced calcium sensitization in SHR. Moreover, fasudil pretreatment shifted norepinephrine dose-response curves to the right more in WKY than in SHR. The additional nifedipine pretreatment shifted these curves further to the right but this shift was more pronounced in SHR than in WKY. Thus adrenergic vasoconstriction is more dependent on L-VDCC in SHR and on RhoA/Rho kinase pathway in WKY rats. CONCLUSION: Ca sensitization mediated by RhoA/Rho kinase pathway is attenuated in SHR compared with normotensive WKY rats. This might be a part of the compensation for enhanced Ca entry through L-VDCC in genetic hypertension.
Keywords: Blood Pressure; Mesenteric Arteries; krevní tlak; rhoA GTP-Binding Protein; oxid dusnatý; potkani inbrední SHR; 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; rho-Associated Kinases; vápník; Calcium Channel Agonists; Rats; Nitric Oxide; Calcium Channels, L-Type; adrenergní receptory; Dose-Response Relationship, Drug; vazokonstrikce; Vasoconstriction; agonisté vápníkových kanálů; Temperature; vztah mezi dávkou a účinkem léčiva; rhoA protein vázající GTP; potkani inbrední WKY; 3-Pyridinecarboxylic acid, 1,4-dihydro-2,6-dimethyl-5-nitro-4-(2-(trifluoromethyl)phenyl)-, Methyl ester; mužské pohlaví; Rats, Inbred WKY; Norepinephrine; kinázy asociované s Rho; Rats, Inbred SHR; Animals; Receptors, Adrenergic; krysa rodu Rattus; Nifedipine; 1-(5-isochinolinsulfonyl)-2-methylpiperazin; Calcium; noradrenalin; 3-pyridinkarboxylová kyselina, 1,4-dihydro-2,6-dimethyl-5-nitro-4-(2-(trifluoromethyl)fenyl)-, methyleste; arteriae mesentericae; Male; nifedipin; zvířata; teplota; vápníkové kanály - typ L